2022
DOI: 10.3390/mi13081240
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Surface-Mounted Devices on Flexible Substrates by Isotropic Conductive Adhesive and Solder and Lifetime Characterization

Abstract: The assembly of passive components on flexible electronics is essential for the functionalization of circuits. For this purpose, adhesive bonding technology by isotropic conductive adhesive (ICA) is increasingly used in addition to soldering processes. Nevertheless, a comparative study, especially for bending characterization, is not available. In this paper, soldering and conductive adhesive bonding of 0603 and 0402 components on flexible polyimide substrates is compared using the design of experiments method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Passive electrical components (PECs) are elements of electrical circuits consisting of laminated solid alloy materials, often drawn in the form of semiconducting wires, that function without a power source but that can dissipate or store electrical power [1,2]. The most common elements are resistors [3][4][5], with the role of delimiting the intensity of the electric current through the electric circuits; capacitors [6], with the role of storing electrical energy in direct current circuits and with the functions of storing electrical and reactive energy in alternating current circuits; and inductors [7], with the role of storing energy in a magnetic field when an electric current flows through it. Other important categories are coils, with resistive functions in direct current circuits, and resistive and reactive functions in alternating current circuits; ferrites, which can be represented as a combination of a coil, a capacitor, and an electrical resistance; potentiometers, defined as variable resistors [8]; varistors [9]; photoresistors [10]; and thermistors [11].…”
Section: Introductionmentioning
confidence: 99%
“…Passive electrical components (PECs) are elements of electrical circuits consisting of laminated solid alloy materials, often drawn in the form of semiconducting wires, that function without a power source but that can dissipate or store electrical power [1,2]. The most common elements are resistors [3][4][5], with the role of delimiting the intensity of the electric current through the electric circuits; capacitors [6], with the role of storing electrical energy in direct current circuits and with the functions of storing electrical and reactive energy in alternating current circuits; and inductors [7], with the role of storing energy in a magnetic field when an electric current flows through it. Other important categories are coils, with resistive functions in direct current circuits, and resistive and reactive functions in alternating current circuits; ferrites, which can be represented as a combination of a coil, a capacitor, and an electrical resistance; potentiometers, defined as variable resistors [8]; varistors [9]; photoresistors [10]; and thermistors [11].…”
Section: Introductionmentioning
confidence: 99%
“…Twelve articles are by authors from China and one paper each was contributed by authors from Germany, Italy, Poland, and Russia. A comprehensive range of aspects related to the structural analyses, designs, and fabrication of flexible/stretchable devices and smart materials are covered, including mechanical analyses of flexible/stretchable devices [ 1 , 2 , 3 , 4 ], thermal analyses of flexible heaters [ 5 , 6 , 7 , 8 , 9 ], mechanical–conductive analyses of island-type structures in flexible/stretchable devices [ 10 ], thermo-mechanical analyses and designs of morphing aircraft structures [ 11 ], adhesive bonding technology for flexible substrates [ 12 ], electrohydrodynamic jet printing technology for flexible substrates [ 13 ], process parameters’ influence on the resistance of 3D-printed electrically conductive structures [ 14 ], and recent advances in flexible radio frequency microelectromechanical systems (RE MEMS) [ 15 ] and triboelectric nanogenerators (TENGs) [ 16 ].…”
mentioning
confidence: 99%
“…Zhang et al [ 11 ] implemented the UMAT in ABAQUS to realize the novel design of a morphing skin with a shape memory alloy based on an equivalent thermal stress approach and investigated the corresponding experiments, with consistent counterpart results. Saleh et al [ 12 ] studied the isotropic conductive adhesive and the solder and lifetime characterization of an assembly of surface-mounted devices on flexible substrates and summarized the better adhesive surfaces for future structural designs. Wang et al [ 13 ] reported on the simulation and printing of microdroplets using a straight electrode-based electrohydrodynamic jet for the flexible substrate, proving the feasibility and high merit of this fabrication technology.…”
mentioning
confidence: 99%